Surveying different alternative metal nanocatalysts for methanol oxidation using facile electrochemical deposition - Ong, Hui Lun (2019)
Commercial electrocatalysts are made using noble metals like platinum (Pt) and palladium (Pd), however these metals are both costly and scarce. Hence, there is interest to investigate the effects of alloying Pd and/or Pt with other metals. This project reports on the exploration of the synthesis and use of different catalysts using the facile stepwise electroless deposition process for the methanol oxidation reaction(MOR). The catalysts were characterised using electrochemical measurements such as cyclic voltammetry (CV) and electrochemically active surface area (ECSA). The experimental results found are then compared against other literature and commercial electrocatalyst like Pt/C and Pd/C.